HUBUNGAN FAKTOR PREDISPOSING, ENABLING DAN REINFORCINGDENGAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA SMA - Harry Sundoro (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
Deviant sexual behavior among unmarried adolescents in terms of reproductive health tends to increase. Premarital sexual behavior in adolescents in high school. The phenomenon of sexual behavior among adolescents according to The Board of Coordinator for National Family Planning in the field as much as 52% had premarital sex.The objective of the research was to find out the correlation of predisposing factors, Enabling and Reinforcing the Pre-Marital Sexual Behavior in Adolescents XY high school in the city of Medan. The research used explanatory method and cross sectional study design. The data were gathered by conducting interviews and questionnaires and analyzed by using multiple logistic regression analysis at α = 0.05.The result of this study showed pre-marital sexual behavior 52.4% of high-risk category. Predisposing factors, 64.5% category is not good knowledge, the attitude of 57.3% in the negative category, socioeconomic 54.0% in the low category. Enabling factors; 54.8% of media access information on exposure category, 58.1% availability of the facilities available in the category. Reinforcing factors; 58.1% of parents have role category, 53.2% of peers have no role category. The result of statistic test showed that predisposing factors (knowledge, attitudes, social and economic) and enabling factors (media access to information and the availability of facilities) as well as reinforcing factors (the role of parents and the role of peers) were correlated (p < 0.05) with the pre sexual behavior marriage. The variable of knowledge had the most dominant correlation with the pre sexual behavior marriage.